Co-creation and collaboration: A promising approach towards successful implementation. Experience from an integrated communication and mental health skills training programme for Japanese General Practice. Issue 10 (October 2021) - van Weel-Baumgarten, Evelyn; Benson, Jill; Hoshi, Goro; Hurle, Clare; Mendive, Juan; Dowrick, Chris; Kassai, Ryuki
Highlights: Involvement of participants, relevant content and local experts in training development improves implementation. Cycles of training and supervision in between training modules add to the effect. Support of a skilled interpreter, sensitive to culture of trainers and participants helps build trust and elicit concerns. Meaningful discussions with all parties involved help to find culturally appropriate solutions and alternatives together. Graphical Abstract: ga1 Abstract: Introduction: This paper describes the co-creation and delivery of an integrated training programme in communication and depression assessment & management for Japanese GPs. Methods: Experts in communication and depression from EACH and WONCA developed a framework and filled it with content. Through iterative discussions with the Japanese participants and experts during delivery, the training was further adjusted to match local needs. It included didactic and experiential training methods with an emphasis on practicing and feedback. A "train-the-trainer" component helped participants develop their own trainer skills to enhance dissemination of the training in Japan. Results: Six Japanese GPs participated in two one week training-modules in May and November 2018. To aid implementation participants received online supervision on depression management and on teaching between the two modules and after the second module. Evaluation of the content of the training, the teaching methods and the participatory approach was positive. More than two years after the training, many elements of the training continue to be used in daily practice with the GPs teaching communication as well as depression management skills. Conclusion: The method of co-creation is promising. Research is needed to confirm that it is effective in transfer to clinical practice.